Persepsi Masyarakat Terhadap Parkir Liar dan Penataan Parkir Di Kabupaten/Kota Bekasi - Sitorus, Budi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2024)
Parking arrangement is intended to regulate traffic flow and maintain order Bekasi. Controlling parking is done through the Department of Transportation and Civil Service in 6 locations, namely Jalan Pramuka, Jalan Veteran, jalan Ir. Juanda. The Path Of Prosperity. The purpose of this study is to determine public understanding of parking, provide recommendations for parking arrangement by utilizing Radio Frequency Identification (RFID). The research method is using qualitative descriptive approach with primary data collection obtained through surveys, using Gay and Diehl data collection techniques with a sample of 18 respondents. The results showed that (1) many people still do not understand regional Regulation Number 11 of 2020 (64.7%), the lack of availability of public transportation so that people choose private vehicles (41.2%), things need to be improved in parking services in Bekasi city by providing adequate public transportation (23%).